2023
DOI: 10.1530/eor-22-0133
|View full text |Cite
|
Sign up to set email alerts
|

Is posterior knee arthroscopy using posterior portals necessary for orthopedic surgeons? The latest evidence on applications and techniques

Abstract: Various uses of posterior knee arthroscopy have been shown, including all-inside repair of posterior meniscal lesions, posterior cruciate ligament (PCL) reconstruction or PCL avulsion fixation, extensile posterior knee synovectomy for pigmented villonodular synovitis or synovial chondromatosis, posterior capsular release in the setting of knee flexion contractures, and loose bodies removal. Posterior arthroscopy provides direct access to the posterior meniscal borders for adequate abrasion and fibrous tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Although anteromedial and anterolateral portals were the most common portals used in diagnostic and therapeutic arthroscopy of the included studies, it has been reported that utilizing anterior portals to visualize structures in the PLC comprising the posterior horn of the LM and PMF is restrictive due to narrow anatomy of posterior section of the knee [21]. Recently, it was recommended to establish posterior arthroscopic portals as they may provide a wider view of posterior structures of the knee and facilitate functional and anatomical fixation of the LM (Figure 3) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although anteromedial and anterolateral portals were the most common portals used in diagnostic and therapeutic arthroscopy of the included studies, it has been reported that utilizing anterior portals to visualize structures in the PLC comprising the posterior horn of the LM and PMF is restrictive due to narrow anatomy of posterior section of the knee [21]. Recently, it was recommended to establish posterior arthroscopic portals as they may provide a wider view of posterior structures of the knee and facilitate functional and anatomical fixation of the LM (Figure 3) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving a complete visualisation of the intra-articular anatomy, particularly focusing on the posterior horn of the medial meniscus, is crucial for making an accurate diagnosis and initiating the appropriate treatment procedure [15]. The posteromedial compartment is identified as one of the primary sources of diagnostic errors in knee arthroscopy, especially in the tight medial tibiofemoral joint [22].…”
Section: Introductionmentioning
confidence: 99%
“…The coating of metal titanium alloy implants (or other metals such as chromium cobalt) is key to improving the bodily response to a metal. As mentioned in Part 1 [ 1 ] of this study, hydroxyapatite (HA) coatings on orthopaedic implants mitigate fibrous build-up and promote implant fixation [ 2 , 3 ]. In this, Part 2 of the study, the evolution of HA as it grows on a substrate and the resulting film is extensively characterised.…”
Section: Introductionmentioning
confidence: 99%